THE MULTICULTURAL PEDAGOGY IN THE PARABLE OF THE GOOD SAMARITAN AND ITS CONTRIBUTION TO SUNDERMEIER’S INTERCULTURAL HERMENEUTIC: A DIACOGNITIVE ANALYSIS - Erni Maria Clartje Efruan; Zummy Anselmus Dami (Analisa: Journal of Social Science and Religion, 2019)
This study was aimed to analyze the text of Luke 10:25-37 using the methods of diacognitive analysis, thus discovering the principles of Jesus’ multicultural pedagogy that can be used as a tool to solve multicultural issues and complement Sundermeier's intercultural hermeneutics so as not to look brittle in its application. The result of the analysis of the Parable of the Good Samaritan suggests that there are five principles in Jesus’ multicultural pedagogy and at once as a contribution to Sundermeier' intercultural hermeneutic, namely: (1). Multicultural issues can only be resolved through the creation of dialogue by the teacher; (2) The teacher's position is decisive in solving multicultural problems; (3) The teacher must know the actual cognition object; (4) The teacher must have multicultural competence; and (5) the primary goal of multicultural pedagogy is reconciliation. Among these five principles, the third principle has the most essential role in its application because it emphasizes compassion. The presence of compassion in teacher' self will make the teacher has a strong desire to help others without considering the differences of ethnicity and religiosity, eliminating assumptions, paying attention to the welfare of others without being selfish, having feel-in and respect, willing to sacrifice both psychic and material to manifest life together (convivencia).